Morphometry of adult cricoid cartilage in Nepalese cadavers: a cross-sectional observational study - Shrestha, Dristi; Adhikari, Bidur; Dwa, Manoranjan; Ranjit, Nirju (Journal of Karnali Academy of Health Sciences, 2026)
Background: Cricoid cartilage is crucial during endotracheal intubation, yet its dimensions in the Nepali population remain uncharacterized. This study aimed to measure cricoid cartilage dimensions in adult Nepalese. Methods: A total of 105 cadavers (75 males, 30 females) were dissected at Department of Forensic Medicine, Maharajgunj Medical Campus, Nepal. Measurements of outer and inner transverse and anteroposterior diameters, as well as heights of the cricoid arch and lamina, were taken using digital vernier callipers. Statistical analyses included gender comparisons and correlations with age. Results: The mean age of the 105 cadavers studied was 34.11 years (SD = 12.08). The measurements of outer anteroposterior diameter, outer transverse diameter, inner anteroposterior diameter, inner transverse diameter, arch height and lamina height were respectively 22mm (SD=4), 21mm (SD=4), 18mm (SD=3), 17mm (SD=3), 9mm (SD=3) and 24mm (SD=4). Inner AP (p = 0.009) and inner TR (p = 0.021) measurements correlated significantly with age. Males had significantly larger cricoid cartilage dimensions than females (p < 0.001). Conclusions: This study provided essential data for selecting appropriately sized ETTs in Nepalese patients, reducing airway complications. It underscored the need to tailor medical devices to local anatomical variations, supporting advancements in biomechanical modelling and medical research